The Impact of TikTok Social Media on the Learning Behavior of Sixth Grade Elementary School Children: A Systematic Literature Review - Agustinus Abraham (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of digital technology and social media, particularly TikTok, has significantly influenced the learning behavior of elementary school students. This study aims to analyze the impact of TikTok use on the learning behavior of sixth-grade elementary school students through a Systematic Literature Review (SLR) approach. Data were collected from Google Scholar following the PRISMA guidelines, resulting in 200 initial articles, which were then selected to obtain 12 articles relevant to the Indonesian context. The synthesis results show that TikTok has a dual impact. On the positive side, TikTok increases creativity, digital skills, self-confidence, interest in learning, and provides access to interesting and interactive educational content. However, excessive use without supervision has negative effects, such as decreased discipline, concentration, and motivation to learn, the emergence of academic procrastination, and changes in behavior and language that are inappropriate. These findings confirm that the influence of TikTok is greatly affected by parental supervision, the role of teachers, digital literacy, and student self-regulation. Therefore, it is necessary to use TikTok wisely, purposefully, and in an integrated manner in educational policies so that its benefits are optimized and its risks can be minimized.